Effect and mechanism of chloride ion on the corrosion behavior of LAZ933 Mg–Li alloy - Yao Tan; Zixue Jiang; Hao Zhang; Junhang Chen; Kui Xiao (Journal of Materials Research and Technology)
This study systematically investigates the corrosion behavior of LAZ933 Mg–Li alloy in chloride-containing environments using a 0.1 wt% NaCl salt spray test, combined with corrosion weight loss analysis, macro-micro-morphological observation, X-ray diffraction (XRD), and electrochemical testing. The results demonstrate that the corrosion rate of LAZ933 Mg–Li alloy gradually decreases with prolonged exposure in the salt spray environment. The surface potential of the α-Mg phase is significantly higher than that of the β-Li phase, resulting in the formation of microcouples at the junction of the two phases to accelerate corrosion. The corrosion product layer is predominantly composed of Mg(OH)2, Li2CO3, and Al2O3. Notably, Li2CO3 and Al2O3 exhibit high stability and corrosion resistance, effectively inhibiting further matrix degradation.